Pembuatan Bioetanol Dari Biji Durian (Durio zibethinus) - Jayanti, Titi; Solfarina, Solfarina (Universitas Tadulako, 2015)
Durian (durio zibethinus) is a tropical plant which is included in the family Malvaceae. The durian flesh is consumed and the durian seed are waste. The purpose of this study was to process durian seeds as raw material for bioethanol production and to determine the levels of ethanol produced from the durian seeds. Fermentation process in this study was conducted using yeast saccharomyces cerevisiae, NPK and urea fertilizers as the starters. After the starters were incubated for two days, then added to the samples and fermented for 5, 8, 11 and 14 days and then distilled. After distilled, the measured ethanol yield, the reaction, with sodium, water dissolued, gravity, and ethanol pH produced. The results showed that fermentation for 5 days derived ethanol content of l5.15%, density 1.08 g/mL, and the pH 3.35. Fermentation for 8 days derived ethanol content of 4.67%, density 0.98 g/mL, and the pH 3.11. Fermentation for 11 days obtained ethanol content of 5.48%, density 0.99 g/mL, and the pH 3.45. Fermentation for 14 days obtained ethanol content of 2.30%, density 1.00 g/mL, and the pH 3.40. This study concluded that durian seeds can be processed into raw material for producing ethanol by fermentation.fermentationfor 5 days was good compared to the 8, 11 and 14 days with ethanol content of 15.15%.